SOFT COMPUTING METHODOLOGIES IN BIOINFORMATICS AND ITS ADVANCE TOWARDS BIOLOGICAL DNA (International Journal of Engineering and Computer Science, 2017)
Bioinformatics is a promising and innovative research field in 21st century. Despite of a high number of techniques specifically dedicated to bioinformatics problems as well as many successful applications, we are in the beginning of a process to massively integrate the aspects and experiences in the different core subjects such as biology, medicine, computer science, engineering, chemistry, physics, and mathematics. Bioinformatics is a fast growing field in the scientific community. It involves a wide range of problems, for example, DNA sequence analyses, RNA secondary structure predictions, phylogenetic analyses and microarray analyses. Recently the use of soft computing tools for solving bioinformatics problems have been gaining the attention of researchers because of their ability to handle imprecision, uncertainty in large and complex search spaces. The paper will focus on soft computing paradigm in bioinformatics. Keywords: Nucleic Acid Sequence, Nucleotides, DNA Sequencing